Inverse filter technique for high-precision ultrasonic pulsed wave range Doppler sensors - Ruser, H.; Vossiek, Martin; von Jena, A.; Magori, V. (IEEE International Conference on Acoustics, Speech, and Signal Processing, IEEE ASSP Conference, 1997)
Ultrasonic pulsed wave range Doppler sensors provide application in various fields, e.g. intruder alarm systems or autonomous vehicle steering. The time-frequency methods commonly used in these sensors, however, inhere the problem that, due to the transducer's non constant and direction-dependent transfer functions, the Doppler frequency cannot be determined with high accuracy needed for such applications. The easiest way to improve the Doppler resolution is to reduce the signal bandwidth, but only at the expense of worse range resolution. In this paper a direction-dependent inverse filter technique is presented, which compensates erroneous effects of the transfer function in the time-frequency analysis. An ultrasonic intruder alarm system determining location and velocity of persons in rooms serves as an example that the novel approach gives evidently better performance than conventional methods, resulting in both high velocity and range resolution.
UnivIS-Import:2015-04-16:Pub.1997.tech.IE.LEH.invers